Non-invasive hydrodynamic characterization of soils using integrated electrical resistivity and x-ray computed tomography - Cimpoiasu, Mihai Octavian (2021)
Current world-wide pressures on farming production can be ameliorated by a more efficient use of agronomical resources. As a root zone is a fundamental component of any agrosystem, it is of high importance to develop a deeper understanding of its processes. One of the key elements of the root zone environment is soil structure, which has a great impact on the capacity of soil to conduct or retain water. This plays a vital role in plant's hydration and nutrient accessibility. As agricultural procedures are continuously developing we require novel methods of monitoring and quantifying their effect on soil structure. Electrical Resistivity Tomography (ERT) is a technique which allows minimally invasive imaging of soil's interior. In the study of soil processes, it is usually applied to monitor changes in soil pore solution concentration, both in space and time. X-ray Computed Tomography (CT) is a method recently adapted for the non-invasive study of soil structure often at high resolutions (e.g. below 50 m). This research aimed to formulate a methodology that combines the capabilities of ERT and X-ray CT in order to enhance our interpretation of soil hydrodynamics by quantitatively linking soil structure and soil pore solution spatiotemporal variability. Furthermore, it intended to apprehend the effects of soil structure on solute infiltration and retention at three different scales: µm scale (observing soil microaggregates), cm scale (observing soil columns) and dm scale (observing agricultural field plots). \\ At the smallest scale, different amounts of distilled water were added to receptacles (2.5x2.5x7 cm) filled with soil. This allowed a distinct water redistribution between samples and subsequent measurements enabled the formulation of a relationship between X-ray absorption and electrical resistivity. This parameter link enables the quantitative crossover between the two soil assessment techniques. At the intermediary scale, columns of soil were X-ray CT scanned and concurrently subjected to the infiltration of a saline solution in near-real time. This allowed patterns of solution percolation to be directly correlated with air-filled porosity distribution. This methodology was applied to two case studies investigating the hydrodynamics of soil columns 1. at different levels of compaction and 2. extracted from agricultural fields under different durations of zero-tillage (ZT) practices (2, 7 and 12 years). The first application revealed and quantitatively correlated the proportionality between areas of underdeveloped macroporosity and lower solution percolation. The second application revealed that soil under ZT for 7 years experienced an initial increase in bulk density, whereas older, 12 years of ZT soil experienced a macroporosity restoration. However, the overall bulk solute dispersivity increased continuously over time indicating preferential flow, but for the 12 year ZT soil, the amount of immobile water content was reduced. Finally, at field scale, hydrodynamics of charcoal enhanced soils were investigated over the course of six months. ERT revealed this soil type had larger variabilities in electrical resistivity than its naturally occurring counterpart. This effect was explained in the context of the X-ray CT analysis of its structure, which revealed a more developed macroporosity, spatially correlated with standard deviation in electrical resistivity. \\ This work has shown what potential a corroborative assessment between two tomographic methods, ERT and X-ray CT, holds for the study of soil's hydraulic properties, revealing new insights about the effect of compaction, ZT and charcoal. Hereafter, future research can expand this methodology for the assessment of plant-soil interactions and soil hydraulic behaviour under different environmental conditions (e.g. soil texture, temperature, root type). Furthermore, the association between the two tomography methods enables the user to visualise solute movement in soil in near real-time together with the solute’s pathway, determined by the soil’s structure. This monitoring approach sets the scene for future work looking to obtain a finer and more discrete parametrization of the soil hydraulic space, which in turn would contribute to a better hydrodynamic representation of soils.